Modulation transfer function (MTF) evaluation for x-ray phase imaging system employing attenuation masks. (7th May 2023) - Havariyoun, Glafkos; Massimi, Lorenzo; Hagen, Charlotte; Endrizzi, Marco; Olivo, Alessandro
Abstract: Objective. Attenuation masks can be used in x-ray imaging systems to increase their inherent spatial resolution and/or make them sensitive to phase effects, a typical example being Edge Illumination x-ray phase contrast imaging (EI-XPCI). This work investigates the performance of a mask-based system such as EI-XPCI in terms of Modulation Transfer Function (MTF), in the absence of phase effects. Approach . Pre-sampled MTF measurements, using an edge, were performed on the same system implemented without masks, with non-skipped masks and finally with skipped masks (i.e. masks in which apertures illuminate every other pixel row/column). Results are compared to simulations and finally images of a resolution bar pattern acquired with all the above setups are presented. Main results . Compared to the detector's inherent MTF, the non-skipped mask setup provides improved MTF results. In comparison to an ideal case where signal spill-out into neighbouring pixels is negligible, this improvement takes place only at specific frequencies of the MTF, dictated by the spatial repetition of the spill-out signal. This is limited with skipped masks, which indeed provide further MTF improvements over a larger frequency range. Experimental MTF measurements are supported through simulation and resolution bar pattern images. Significance . This work has quantified the improvement in MTF due to the use of attenuation masks and lays the foundation for how acceptance and routine quality control tests will have to be modified when systems using masks are introduced in clinical practice and how MTF results will compare to those of conventional imaging systems.